2020
DOI: 10.1017/dsd.2020.68
|View full text |Cite
|
Sign up to set email alerts
|

Toward Hybrid Teams: A Platform to Understand Human-Computer Collaboration During the Design of Complex Engineered Systems

Abstract: Human-computer hybrid teams can meet challenges in designing complex engineered systems. However, the understanding of interaction in the hybrid teams is lacking. We review the literature and identify four key attributes to construct design research platforms that support multi-phase design, hybrid teams, multiple design scenarios, and data logging. Then, we introduce a platform for unmanned aerial vehicle (UAV) design embodying these attributes. With the platform, experiments can be conducted to study how des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Behavioural analyses in that previous work by the authors revealed that AI-assisted teams exhibited greater agility in adapting to structural shocks, performed fewer but more meaningful design actions, and explored more of the design space than human-only teams (Song et al, 2020). While only a preliminary analysis on team communication was conducted, this current work aims to expand that analysis to deepen the understanding of this fundamental process of AI-assisted human teams, specifically focusing on the discourse among the human team members.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Behavioural analyses in that previous work by the authors revealed that AI-assisted teams exhibited greater agility in adapting to structural shocks, performed fewer but more meaningful design actions, and explored more of the design space than human-only teams (Song et al, 2020). While only a preliminary analysis on team communication was conducted, this current work aims to expand that analysis to deepen the understanding of this fundamental process of AI-assisted human teams, specifically focusing on the discourse among the human team members.…”
Section: Introductionmentioning
confidence: 85%
“…The business discipline, consisting of a business manager, operations manager and design manager, focuses on market targeting; the operations discipline, consisting of two operations specialists and one operations manager, focuses on drone path planning; while the design discipline, consisting of one design specialist and one design manager focuses on drone design. More detailed descriptions regarding the experimental platform, problem statement, roles, and experimental methodology can be found in related work (Song et al, 2020).…”
Section: Drone Design Studymentioning
confidence: 99%
“…Importantly, participants configure, test, and share their designs and communicate with their teammates in these experiments through an online research platform, called HyForm. 1 The architecture of the platform and the detailed information of the design and operation AI agents integrated in the platform are found in prior research [1] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Depending on the role, each participant has access to one of the following three interface modules. More details of each module are found in the prior research [1] . The drone design module enables members of the design team to construct drones.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…AI cannot effectively learn and replicate creativity [37], interpersonal empathy [38], [39], intuition [40], knowledge consolidation or persuasion for problem-solving, or to coordinate and lead teams [41], [42]. AI cannot fully replace human designers because of their lack of creativity and agility, which is needed to solve complex engineering design problems [43]. Computerizing creativity is limited by the programmer's ability to define the creative values clearly to be encoded into an algorithm [44].…”
Section: Limitations Of Ai In Engineering Designmentioning
confidence: 99%